Examination of the Condition of Ijtihād in the Role of Arbitration - Hosein Houshmand Firouzabadi; Muhammad Javad Ghasemizadegan; ehsan yavari (آموزه‌‌های فقه مدني, 2024)
The method of dispute resolution through arbitration is popular and increasingly widespread due to its nature as a quick, specialized, and a form of private adjudication based on the parties’ will. Despite the well-known opinion of the jurists who maintain that it is necessary for an arbitrator to have ijtihād (Arabic: اجْتِهاد, lit.: physical effort or mental effort) just as it is required for an appointed judge, some jurists have not accepted this. In law, although there is an emphasis on the necessity for the arbitrator to have expertise regarding the disputes referred to him, ultimately the will of the parties can disregard the necessity of having this expertise and assign arbitration to a non-specialist. This article examines the legal requirement of ijtihad in arbitration, drawing upon the principles of Imāmiyya (Arabic: امامیّه) jurisprudence. Specifically, we seek to determine whether, from a jurisprudential perspective, ijtihād (physical effort or mental effort) is a necessary qualification for arbitrators, akin to the requirement for appointed judges. To explore the issue at hand, it’s essential to clarify the exact nature of taḥkīm (Arabic: تَحْکیم, Islamic arbitration) and legal arbitration. This article, using a descriptive-analytical approach, first investigates the concept of arbitration and highlights the overlap between the “arbitration” institution in law and “arbitration judgment” (Persian: قضاوت تحْکیمی) in jurisprudence. Among the various views on whether ijtihād (intellectual effort) is required for arbitrators, the article adopts the theory of distinction. This theory suggests that ijtihad is not necessary for minor claims and those involving personal rights (Ḥaqq al-Nās) but is required for other types of disputes and claims. The theory is supported by three main arguments: firstly, disregarding the specific context mentioned in  Imām ʿAlī (ʿalayhi s-salāmu)’s narration; secondly, considering the suitability of the ruling and subject from the perspective of custom; and thirdly, recognizing the specialized nature of the arbitration process. Other theories are set aside based on these considerations.